The Potential of Strawberry, Rome Beauty Apple, and New Combination on Fasting Blood as Supporting Diet Therapy in Patients with Type II Diabetes Mellitus - Niken Yuliwati; Riezky Faisal Nugroho (Universitas Islam Bandung, 2021)
Strawberries (Fragaria x ananassa) and Rome beauty apples (Malus sylvestris) contain high antioxidants to reduce oxidative stress and improve the glycemic response with diabetes mellitus (DM) type II. This study aimed to analyze the effect of strawberries, Rome beauty apples, and their combination to decrease fasting blood glucose levels of type II DM patients. This experimental research used a randomized pre-post-test with a control group design. Subjects were 44 patients divided into four groups: K (control, not given the fruit), P1 (strawberries 200 g/day), P2 (apples 300 g/day), and P3 (the combination strawberries 100 g/day, apples 150 g/day) for 14 days in February–March 2019 in Surakarta. The inclusion criteria were DM patients aged 40–55 years who received oral antidiabetic drug therapy. Exclusion criteria were type II DM patients who, based on the doctor's diagnosis, had complications such as gastritis, hypertension, chronic renal failure, heart disease, liver disease, stroke, cancer, patients with consumption of antioxidant supplements. Mean of blood glucose level on K (149.82±39.125), P1 (141.00±38.079), P2 (128.73±31.841), and P3 (177.73±50.176). Analysis paired t test results showed a significant difference between before and after treatment (p=0.045). To find out which group was the most meaningful, the Bonferroni post hoc test. Decrease of fasting blood glucose levels with group K (−10.55, p>0.05), P1 (−30.18, p<0.05), P2 (40.27, p<0.05), and P3 (−32.91, p<0.05). ANOVA test was used to analyze, and the post hoc Bonferroni test with a control comparison was performed, resulting in p=0.028, in P2 and p>0.05 in P1 and P3. In conclusion, strawberries, Rome beauty apples, and their combination significantly decreased fasting blood glucose levels of type II DM patients, with the highest and most significant decrease in Rome beauty apples. POTENSI STROBERI, APEL ROME BEAUTY, DAN KOMBINASI BARU TERHADAP GULA DARAH PUASA SEBAGAI PENUNJANG TERAPI DIET PADA PASIEN DIABETES MELITUS TIPE IIStroberi (Fragaria x ananassa) dan apel Rome beauty (Malus sylvestris) mengandung antioksidan tinggi untuk mengurangi stres oksidatif dan memperbaiki respons glikemik pada diabetes melitus (DM) tipe II. Tujuan penelitian adalah menganalisis pengaruh buah stroberi, apel Rome beauty, dan kombinasinya terhadap penurunan kadar glukosa darah puasa pasien DM tipe II. Jenis penelitian eksperimen dengan rancangan randomized pre-post-test dengan control group design. Subjek penelitian 44 pasien yang dibagi empat kelompok, yaitu K (kontrol tidak diberi buah), P1 (stroberi 200 g/hari), P2 (apel Rome beauty 300 g/hari) dan P3 (kombinasi stroberi 100 g/hari dan apel 150 g/hari) selama 14 hari pada bulan Februari–Maret 2020 di Surakarta. Kriteria inklusi adalah pasien DM usia 40–55 tahun yang mendapat terapi obat antidiabetik oral. Kriteria eksklusi adalah pasien DM tipe II yang berdasar atas diagnosis dokter mengalami komplikasi seperti mag, hipertensi, gagal ginjal kronik, penyakit jantung, penyakit hati, strok, kanker, dan pasien dengan konsumsi suplemen antioksidan. Kadar glukosa darah rerata pada K (149,82±39,125), P1 (141,00±38,079), P2 (128,73±31,841), dan P3 (177,73±50,176). Hasil analisis paired t test menunjukkan terdapat perbedaan yang signifikan antara sebelum dan sesudah perlakuan (p=0,045). Untuk mengetahui kelompok mana yang paling bermakna, dilakukan Uji Post Hoc Bonferroni. Penurunan kadar glukosa darah puasa pada K (−10,55; p>0,05), P1 (−30,18; p<0,05), P2 (−40,27; p<0,05), dan P3 (−32,91; p<0,05). Analisis dilakukan dengan uji ANOVA dan Uji Post Hoc Bonferroni dengan perbandingan kontrol menghasilkan p=0,028 pada P2 serta p>0,05 pada P1 dan P3. Simpulan, pemberian stroberi, apel Rome beauty, dan kombinasinya signifikan menurunkan kadar glukosa darah puasa pasien DM tipe II dengan penurunan tertinggi dan bermakna pada apel Rome beauty.